Development of Marl Soap and Marl Mixed with Butterfly Pea Flower Extract Soap - Phansi, Piyawan; Klaythongpan, Pimmada (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2024)
This research aimed to develop glycerin soap products containing marl, a raw material abundantly produced in Lopburi province, and butterfly pea flower extract (Clitoria ternatea L.). The physical and chemical properties of seven different soap formulations were studied and compared. The results of the study indicated that the soap has no foreign substances. The color values expressed as L*, a* and b* of the marl soap ranged from 62.99±0.40 to 69.50±0.29, 0.26±0.04 to 1.41±0.13, and 8.05±0.23 to 11.73±0.51, respectively. For the soap containing marl and butterfly pea extract, the L*, a*, and b* values ranged from 44.78±1.19 to 55.34±1.51, -11.75±0.01 to -7.78±0.52, and 1.12±0.28 to 2.93±0.60, respectively. The color values for the soap containing marl, butterfly pea, and turmeric extracts, the L*, a*, and b* values were 40.90±0.28, 6.65±0.09, and 27.27±0.44, respectively. All soap formulas exhibited bubble volume values ranging from 72.67±1.53 to 75.00±2.18 mL, bubble durability from 68.50±1.32 to 71.67±2.52 mL, erosion percentage from 15.52±1.78 to 16.57±1.75, and pH values between 9.70 to 9.86. The antioxidant activity of the soap, compared to the ascorbic acid standard, ranged from 2.16±0.11 to 4.65±0.36 AAE/gram of soap. Soap with added butterfly pea extract and turmeric demonstrated higher antioxidant activity than the control soap. The satisfaction assessment results for the soap products and packaging among a sample of 20 people were very satisfactory. Therefore, the developed soap can be used as a prototype product for the community.